Phytochemical Screening of Honey Pineapple Peel Extract and Its Application as an Antibacterial Additive in Dish Soap Formulation - Elfi Susanti VH; Sri Mulyani; Sri Retno Dwi Ariani; Suryadi Budi Utomo; Bayu Antrakusuma (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
This research aims to scientifically develop bioactive compounds from honey pineapple peel and develop a dish soap formulation with extract additives of honey pineapple peel that can be antibacterial. The research was conducted in stages, namely process of extracting honey pineapple peel was carried out by the maceration method using 96% ethanol as a solvent, phytochemical screening of the ethanol extract of honey pineapple peel was done to determine the class of compounds contained in the extract, and application of honey pineapple peel extract in dish soap formulation was to obtain a dish soap formulation with optimal antibacterial activity. Testing the ability of dish soap products to inhibit S. aureus bacteria was performed by the method of filter paper disc diffusion. The results revealed that the ethanol extract of honey pineapple peel contained alkaloids, flavonoids, tannins, and saponins. The ethanol extract of honey pineapple peel has been applied in a dish soap formulation and tested for the antibacterial activity of S. aureus. Antibacterial test results showed that the dish soap formulation with the addition of 5% pineapple peel extract provided strong antibacterial activity, indicated by a precise zone formation of 12.60 mm